PENANGANAN SAMPAH RUMAH TANGGA DI DESA X KABUPATEN BANDUNG - Aprileni, Fitri Mukhilsah; Nurhayati, Ati (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
The community in Village X has not carried out garbage sorting behavior. In addition, garbage collection is carried out once a week which causes waste to accumulate in community settlements and do not have TPS (Temporary Shelters). The aim of the study was to determine waste generation, waste handling at the sorting stage, container, collection, transportation, infrastructure, as well as knowledge and behavior of respondents towards waste handling. This type of research is descriptive. Approach through surveys and observations. A sample of 75 people and 6 houses with a total of 29 people were used as samples for waste generation. The results of measurements of waste generation for 6 houses for 8 days were 0.169 kg/person/day. The sorting stage 47% have done the sorting, 53% did not do the sorting, 47% container met the requirements, 53% did not meet the requirements, collection did not meet the requirements of 100% and transportation did not meet the requirements of 100%. TPS infrastructure 58.4% met the requirements and 41.6% did not meet the requirements. The knowledge level of the respondents was 61 in the good category, 13 in the sufficient category and 1 in the poor category, while the behavior of 39 was in the good category, 12 was in the sufficient category and 22 was in the poor category. Suggestions for managers to conduct outreach about waste handling, increase the schedule for collecting and transporting waste.